منهج تناول اليهودية عند أحمد شلبي وعرفان عبد الحميد: دراسة مقارنة - بلوي، موسى بن عبد الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research aims at studying the features and characteristics of the method of authorship in the Jewish religion according to both Ahmad Shalabi and 'Irfan Abdul HamidFattah, whereby using a comparative approach between their writings in the field of comparative religions in general, and Judaism in particular. The research contains five chapters and a conclusion. The first chapter is for the research proposal and its general structure, and the second chapter focuses on the definition of the Jewish religion and the methodology (ies) of the Muslim scholars in its study. The third and fourth chapters, respectively, deal with the biography, the writings of these two scholars and their methodology in the writing on Judaism as well as the sources and references used by them in this study. The last chapter of the research studies the aspects of agreement and disagreement between their methodologies. This research achieved the following findings: the works of both Ahmad Shalabi and ''Irfan Abdul Hameed are characterized with original and vast knowledge on Judaism. Their recognition and knowledge of a number of foreign languages has played a prominent role in their way of thinking. They are distinguished in the study of Judaism by applying the historical and descriptive approachs, as well as their use of objective criticism. The researcher found some differences between Ahmad Shalabi and ''Irfan Abdul Hameed in relation with the content of their books on Judaism. According to the researcher, both Ahmad Shalabi and ''Irfan Abdul Hameed relied on comparative analytical approach in addition to the historical approach, which is the dominant one in their books. In addition, the convergence in the quality of their sources is often the result of similarity of their methodology.